Manifestation of Professional Resistance in Social Work - Šumskienė, Eglė; Mataitytė-Diržienė, Jurga; Samoškaitė, Vitalija (Socialinė teorija, empirija, politika ir praktika, 2025)
Professional resistance refers to actions taken by social workers against systemic barriers that hinder the fulfilment of their professional mission, as well as opposition to unfavourable laws or practices. The aim of the article is to examine the premises and manifestations of professional resistance among social workers in Lithuania. The first part of the article discusses the origins and development of research on professional resistance in social work and establishes a theoretical framework for analyzing social workers’ resistance. The empirical section presents the results of a survey conducted with 181 social workers, focusing on the forms of resistance they use, the motivating factors behind their resistance, and the consequences associated with these actions. The study revealed that resistance reflects social workers’ commitment to defending the interests of service users and adhering to professional ethical standards, even when it involves confronting institutional or professional barriers.